House/Senate Conference on S. 304, National Tourism Policy Act. (U.S. G.P.O.], 1981)
Joint meeting to consider S. 304, the National Tourism Policy Act, to establish a national tourism policy and a U.S. Travel and Tourism Administration within the Department of Commerce.